Revitalisasi Dana Menganggur dalam Ekonomi Islam: Analisis Prinsip Iktinaz dan Arah kebijakan moneter Ekspansif - Nasrudin; Nursari, Nina; Nurzannah, Firda; Hidayah, Paisah Nurul; Priatna, Elya Nur Awaliyah Fadhilah Fatimah (Jurnal Ilmiah Ekonomi Islam, 2026)
The phenomenon of idle funds amounting to Rp457.5 trillion stored at Bank Indonesia reflects the inefficiency of the financial system and the weak transmission of monetary policy to the real sector. From an Islamic economic perspective, this condition represents the practice of iktinaz or hoarding of wealth without social benefit, which contradicts the principle of maqāṣid al-syarī‘ah, especially the aspect of tadāwul al-māl (circulation of wealth). This study aims to analyse the concept of iktinaz in the context of modern economics and to offer directions for an expansionary monetary policy grounded in Islamic values. This study uses a qualitative method with a normative approach and content analysis of national macroeconomic data and Bank Indonesia's monetary policy.. The results show that idle funds are not only a technical liquidity issue but also a crisis of values in wealth management. Therefore, the revitalisation of idle funds can be achieved through Islamic monetary instruments such as productive sukuk, qard al-hasan, and cash waqf-linked sukuk, which can encourage the circulation of funds to the productive sector. The novelty of this research lies in formulating a Sharia monetary policy that integrates moral, spiritual, and economic dimensions. Its contribution offers a new paradigm of Islamic monetary policy oriented towards distributive justice and financial sustainability.